Left Ventricular Assist Device Management in the Emergency Department - Paul Trinquero; Andrew Pirotte; Lauren P. Gallagher; Kimberly M. Iwaki; Christopher Beach; Jane E. Wilcox (Western Journal of Emergency Medicine, 2018)
The prevalence of patients living with a left ventricular assist device (LVAD) is rapidly increasing due to improvements in pump technology, limiting the adverse event profile, and to expanding device indications. To date, over 22,000 patients have been implanted with LVADs either as destination therapy or as a bridge to transplant. It is critical for emergency physicians to be knowledgeable of current ventricular assist devices (VAD), and to be able to troubleshoot associated complications and optimally treat patients with emergent pathology. Special consideration must be taken when managing patients with VADs including device inspection, alarm interpretation, and blood pressure measurement. The emergency physician should be prepared to evaluate these patients for cerebral vascular accidents, gastrointestinal bleeds, pump failure or thrombosis, right ventricular failure, and VAD driveline infections. Early communication with the VAD team and appropriate consultants is essential for emergent care for patients with VADs.